Examination of the larynx in the histopathology laboratory. Issue 8 (August 1980) - Michaels, L; Gregor, R T
Abstract : A method is described for examination of the larynx in the histopathology laboratory. Using a slicing machine, transverse slices of the whole larynx are obtained from which representative histological samples may be prepared. This method offers the advantages of a complete gross examination of the normal and pathological structures of the larynx supplemented by histological studies using any of the methods of paraffin embedding, frozen section, plastic embedding, or electron microscopy on any part of the larynx.